Paulina Sosnowska: Hannah Arendt and Martin Heidegger. Philosophy, Modernity, and Education, Lanham/Boulder/New York: Lexington Books 2019. : The retelling of an intellectual relationship - Meisel, Sebastian (HannahArendt.net, 2022)
It is a common topos that the relationship between Hannah Arendt and Martin Heidegger was a special one; studies about their connection fill entire shelves as an object of scholarly and biographical research. So, what is the reason for retelling this story of intellectual influence, which, as we know, was highly one-sided? First and foremost, because new questions are constantly being raised and this affair has neither been concluded nor discussed in its entirety.